Scrotal Epidermoid Cyst Presenting as Extra-Testicular Scrotal Mass: A Diagnostic Dilemma - Shirale Vaishali; Goyal Sunder; Tyagi Vikas; Goyal Snigdha (Journal of Spleen And Liver Research, 2020)
We hereby report a scrotal epidermoid cyst presenting as a scrotal mass which a rare entity in the absence of trauma. 36years old male presents with a complaint of left sided testicular swelling and discomfort. The workup included clinical examination, alpha-fetoprotein (αFP) and beta-human chorionic gonadotropin (β-hCG) analyses and scrotal ultrasound. Clinically confused as testicular malignancy. Complete surgical excision of the cyst was performed. Histopathology confirmed epidermoid cyst with no evidence of malignancy.
Keywords: epidermoid Cyst